2021
DOI: 10.3390/v13091680
|View full text |Cite
|
Sign up to set email alerts
|

New Resources for the Specific and Sensitive Detection of the Emerging Tomato Brown Rugose Fruit Virus

Abstract: Plant viruses can evolve towards new pathogenic entities that may eventually cause outbreaks and become epidemics or even pandemics. Seven years ago, tomato brown rugose fruit virus (ToBRFV) emerged, overcoming the genetic resistance that had been employed for more than sixty years against tobamoviruses in tomato. Since then, ToBRFV has spread worldwide, producing significant losses in tomato crops. While new resistances are deployed, the only means of control is the implementation of effective prevention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…The ToBRFV and ToMMV duplex assay (Duplex B) included in the validation process according to [38] was evaluated in terms of analytical sensitivity and specificity, selectivity, repeatability, and reproducibility. The LODs obtained for both leaf (10 −6 /10 −5 ) and seed (10 −5 ) matrices and for both target viruses were in line with those of other real-time RT-PCR tests for the detection of tobamovirus species [20,40,41]. In addition, the performance criteria when testing dilution series (leaf or seeds samples) showed that there was no relevant reduction in LOD and/or primer efficiency (E) for the duplex assay compared to the single assays.…”
Section: Discussionsupporting
confidence: 85%
“…The ToBRFV and ToMMV duplex assay (Duplex B) included in the validation process according to [38] was evaluated in terms of analytical sensitivity and specificity, selectivity, repeatability, and reproducibility. The LODs obtained for both leaf (10 −6 /10 −5 ) and seed (10 −5 ) matrices and for both target viruses were in line with those of other real-time RT-PCR tests for the detection of tobamovirus species [20,40,41]. In addition, the performance criteria when testing dilution series (leaf or seeds samples) showed that there was no relevant reduction in LOD and/or primer efficiency (E) for the duplex assay compared to the single assays.…”
Section: Discussionsupporting
confidence: 85%
“…In fact, the other pre-tested sets developed in this study and targeting CP region, reacted unspecifically with CGMMV, a tobamovirus that infects Cucurbitaceae plant species, and a very limited number of Solanaceae species [43]. (10 -6 /10 -5 ) and seed (10 -5 ) matrices and for both target viruses were in line with those of other real-time RT-PCR tests for the detection of tobamovirus species [22,44,45]. In addition, the performance criteria when testing dilution series (leaf or seeds samples) showed that there was no relevant reduction in LOD and/or primer efficiency (E) for the duplex assay compared to the single assays.…”
Section: Discussionsupporting
confidence: 71%
“…Outcomes of the TPS are available through the EPPO database on diagnostic expertise (https://dc.eppo.int/validation_data/validationlist). In this revised version of the protocol, two additional tests have been included: Panno et al (2019b) which was evaluated in VALITEST, and Bernabé‐Orts et al (2021) which targets a different part of the ToBRFV genome compared to the tests evaluated in the framework of VALITEST.…”
Section: Detectionmentioning
confidence: 99%